Clinical outcomes in end stage renal disease on dialysis and severe coronary artery disease: A real-world study. (1st May 2023) - Koh, Samuel Ji Quan; Yap, Jonathan; Jiang, Yilin; Sng, Gerald Gui Ren; Low, Yi Hua; Lau, Yee How; Sin, Yoong Kong Kenny; Yeo, Khung Keong
Abstract: Background: The optimal management of patients with end-stage renal disease (ESRD) on dialysis with severe coronary artery disease (CAD) has not been determined. Methods: Between 2013 and 2017, all patients with ESRD on dialysis who had left main (LM) disease, triple vessel disease (TVD) and/or severe CAD for consideration of coronary artery bypass graft (CABG) were included. Patients were divided into 3 groups based on final treatment modality: CABG, percutaneous coronary intervention (PCI), optimal medical therapy (OMT). Outcome measures include in-hospital, 180-day, 1-year and overall mortality and major adverse cardiac events (MACE). Results: In total, 418 patients were included (CABG 11.0%, PCI 65.6%, OMT 23.4%). Overall, 1-year mortality and MACE rates were 27.5% and 55.0% respectively. Patients who underwent CABG were significantly younger, more likely to have LM disease and have no prior heart failure. In this non-randomized setting, treatment modality did not impact on 1-year mortality, although the CABG group had significantly lower 1-year MACE rates (CABG 32.6%, PCI 57.3%, OMT 59.2%; CABG vs. OMT p < 0.01, CABG vs. PCI p < 0.001). Independent predictors of overall mortality include STEMI presentation (HR 2.31, 95% CI 1.38–3.86), prior heart failure (HR 1.84, 95% CI 1.22–2.75), LM disease (HR 1.71, 95% CI 1.26–2.31), NSTE-ACS presentation (HR 1.40, 95% CI 1.03–1.91) and increased age (HR 1.02, 95% CI 1.01–1.04). Conclusion: Treatment decisions for patients with severe CAD with ESRD on dialysis are complex. Understanding independent predictors of mortality and MACE in specific treatment subgroups may provide valuable insights into the selection of optimal treatment options. Highlights: Patients with ESRD on dialysis have a significant burden of adverse outcomes with no optimal treatment option identified. In the real-world, treatment decisions for these patients are complex, taking into account both physician considerations and patient's preference and comorbidities. In this observational study, patients who eventually undergo CABG represent the minority. Understanding the independent predictors of mortality and MACE in specific treatment subgroups may provide valuable insights into the selection of the optimal treatment options.